Effects of Nd : YAG and Er : YAG lasers on the sealing of root canal fillings - Carvalho, CAT; Valera, M. C.; Gown-Soares, S.; Eduardo, C. D. (Mary Ann Liebert, Inc., 2002)
Objective: the ability of the laser irradiation to promote the cleaning and disinfection of the radicular canal system has become this type of treatment in a viable and real alternative in endodontics. The purpose of this study was to evaluate the apical marginal sealing of root canal fillings after the irradiation with the laser of Nd:YAG or of Er:YAG. Materials and Methods: Forty-two human, extracted single-rooted teeth had their crowns sectioned and the root canals prepared with a no. 70 K-file. Then, they were dried and divided into three groups according to canal wall treatment: group 1: the canals were filled with EDTA for 3 min, followed by irrigation with 1% sodium hypochlorite solution; group 2: the canal walls were irradiated with Nd:YAG laser; and group 3: the canal walls were irradiated with Er:YAG laser. Afterwards, the root canals were obturated by the lateral condensation technique. The roots were externally waterproof, except in the apical foramen and immerged in 2% methylene blue aqueous solution during 48 hours. Results: the results showed that the largest infiltrations happened in the group 3-Er:YAG (7.3 mm), proceeded by the group 1-EDTA (1.6 mm) and by the group 2-Nd:YAG (0.6 mm). The group Er:YAG differed statistically of the others (p < 0.05). Conclusion: It was concluded that the Er:YAG laser intracanal irradiation previously to the root canal filling must be used with caution until future research is define the best parameters for it's use.